Peroxisomes: versatile organelles with diverse roles in plants. Issue 4 (26th September 2019) - Pan, Ronghui; Liu, Jun; Wang, Saisai; Hu, Jianping
Summary: Peroxisomes are small, ubiquitous organelles that are delimited by a single membrane and lack genetic material. However, these simple‐structured organelles are highly versatile in morphology, abundance and protein content in response to various developmental and environmental cues. In plants, peroxisomes are essential for growth and development and perform diverse metabolic functions, many of which are carried out coordinately by peroxisomes and other organelles physically interacting with peroxisomes. Recent studies have added greatly to our knowledge of peroxisomes, addressing areas such as the diverse proteome, regulation of division and protein import, pexophagy, matrix protein degradation, solute transport, signaling, redox homeostasis and various metabolic and physiological functions. This review summarizes our current understanding of plant peroxisomes, focusing on recent discoveries. Current problems and future efforts required to better understand these organelles are also discussed. An improved understanding of peroxisomes will be important not only to the understanding of eukaryotic cell biology and metabolism, but also to agricultural efforts aimed at improving crop performance and defense.